ASD and PDA closure with CeraTM and CeraFlexTM devices - Buys, D.G.; Greig, C.; Brown, S.C. (SA Heart Journal, 2017)
Introduction and aim: Percutaneous closure of congenital cardiac defects is common practice. The aim of the study was to describe our experience in closing PDAs, PFOs and an ASD using the new CeraTM and CeraFlexTM devices. Methods: Twenty patients were included in this retrospective review. All patients underwent device closure with the Cera TM and CeraFlexTM devices. Results: All attempts at device closure were successful (n=20). Indications included PDA (n=16), ASD (n=1) and PFO (n=3). Median age at procedure was: PDA 1y 10mo (4mo - 10y 4mo), ASD 27y and PFO 50y 9mo (38y - 70y). Median weight at procedure was: PDA 10.5kg (4.9kg - 70kg), ASD 56kg and PFO 82.5kg (80kg - 113kg). Periprocedural complications consisted of embolisation of 2 PDA devices, which could be repositioned. Conclusion: The CeraTM and CeraFlexTM devices are effective for closure of PDAs, ASDs and PFOs.